Insulin Signaling in Human Visceral and Subcutaneous Adipose Tissue In Vivo - Laviola, Luigi; Perrini, Sebastio; Cignarelli, Angelo; Natalicchio, Annalisa; Leonardini, Anna; De Stefano, Francesca; Cuscito, Marilena; De Fazio, Michele; Memeo, Vincenzo; Neri, Vincenzo; Cignarelli, Mauro; Giorgino, Riccardo; et al. (Diabetes (New York, N.Y.), 2006)
Insulin Signaling in Human Visceral and Subcutaneous Adipose Tissue In Vivo Luigi Laviola 1 , Sebastio Perrini 1 , Angelo Cignarelli 1 , Annalisa Natalicchio 1 , Anna Leonardini 1 , Francesca De Stefano 1 , Marilena Cuscito 1 , Michele De Fazio 2 , Vincenzo Memeo 2 , Vincenzo Neri 3 , Mauro Cignarelli 4 , Riccardo Giorgino 1 and Francesco Giorgino 1 1 Department of Emergency and Organ Transplantation, Section of Internal Medicine, Endocrinology and Metabolic Diseases, University of Bari, Bari, Italy 2 Department of Emergency and Organ Transplantation, Section of General Surgery, University of Bari, Bari, Italy 3 Division of General Surgery, University of Foggia, Foggia, Italy 4 Division of Endocrinology, University of Foggia, Foggia, Italy Address correspondence and reprint requests to Francesco Giorgino, MD, PhD, Department of Emergency and Organ Transplantation, Section of Internal Medicine, Endocrinology and Metabolic Diseases, University of Bari, Piazza Giulio Cesare, 11, I-70124 Bari, Italy. E-mail: f.giorginoatendo.uniba.it Abstract In this study, we evaluated the activation of various insulin signaling molecules in human fat in vivo and compared signaling reactions in visceral and subcutaneous fat depots. Paired abdominal omental and subcutaneous fat biopsies were obtained from nonobese subjects with normal insulin sensitivity under basal conditions and 6 and 30 min following administration of intravenous insulin. Insulin receptor phosphorylation was more intense and rapid and insulin receptor protein content was greater in omental than in subcutaneous adipose tissue ( P < 0.05). Insulin-induced phosphorylation of Akt also occurred to a greater extent and earlier in omental than in subcutaneous fat ( P < 0.05) in the absence of significant changes in Akt protein content. Accordingly, phosphorylation of the Akt substrate glycogen synthase kinase-3 was more responsive to insulin stimulation in omental fat. Protein content of extracellular signal–regulated kinase (ERK)-1/2 was threefold higher in omental than in subcutaneous fat ( P < 0.05), and ERK phosphorylation showed an early 6-min peak in omental fat, in contrast with a more gradual increase observed in subcutaneous fat. In conclusion, the adipocyte insulin signaling system of omental fat shows greater and earlier responses to insulin than that of subcutaneous fat. These findings may contribute to explain the biological diversity of the two fat depots. ERK, extracellular signal–regulated kinase GAPDH, glyceraldehyde-3-phosphate dehydrogenase GSK, glycogen synthase kinase IRS, insulin receptor substrate ITT, insulin tolerance test MAP, mitogen-activated protein PAI-1, plasminogen activator inhibitor 1 PI, phosphatidylinositol PPAR, peroxisome proliferator–activated receptor Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted January 18, 2006. Received October 29, 2005. DIABETES